2024
DOI: 10.1001/jamapediatrics.2024.0001
|View full text |Cite
|
Sign up to set email alerts
|

Heat Exposure, Preterm Birth, and the Role of Greenness in Australia

Tingting Ye,
Yuming Guo,
Wenzhong Huang
et al.

Abstract: ImportancePreterm birth (PTB) is associated with adverse health outcomes. The outcomes of heat exposure during pregnancy and the moderating association of greenness with PTB remain understudied.ObjectiveTo investigate associations between heat exposure, greenness, and PTB, as well as interactions between these factors.Design, Setting, and ParticipantsIncluded in this cohort study were births occurring in Sydney, New South Wales, Australia, between 2000 and 2020, retrieved from New South Wales Midwives Data Col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 45 publications
0
0
0
Order By: Relevance
“…Encouraging outdoor exploration, nature-based activities, and environmental stewardship can help children develop a deeper appreciation for the natural world and a stronger commitment to protecting it (Pérez-del-Pulgar et al, 2021 ). Studies have shown that spending time in nature can reduce stress, improve mood, and boost cognitive function (Ye et al, 2024 ) even in subjects with neuropsychiatric disorders (Curzio et al, 2022 ). Connecting children with the natural world can not only improve their mental health but also empower them to become active participants in finding solutions to the climate crisis.…”
Section: Establishing Community Hubs For Building a Cultural And Educ...mentioning
confidence: 99%
“…Encouraging outdoor exploration, nature-based activities, and environmental stewardship can help children develop a deeper appreciation for the natural world and a stronger commitment to protecting it (Pérez-del-Pulgar et al, 2021 ). Studies have shown that spending time in nature can reduce stress, improve mood, and boost cognitive function (Ye et al, 2024 ) even in subjects with neuropsychiatric disorders (Curzio et al, 2022 ). Connecting children with the natural world can not only improve their mental health but also empower them to become active participants in finding solutions to the climate crisis.…”
Section: Establishing Community Hubs For Building a Cultural And Educ...mentioning
confidence: 99%